Natural disasters and domestic violence?: A study of the 2015 Nepal earthquake - ARPITA KHANNA, (Institutional Knowledge at Singapore Management University, 2022)
This study estimates the impact of exposure to the 2015 Nepal Earthquake on intimate partner violence with two rounds of Demographic and Health Surveys data. Using differences-in-differences estimation, we find that exposure to the earthquake lead to a statistically and economically significant increase in intimate partner violence in the urban areas but not in the rural areas. This is possibly due to an increase in the stress felt by the earthquake victims. We also offer some evidence that the impact heterogeneity between the urban and rural areas is attributable to the differences in the reconstruction processes and assistance provided.